Study Of The Effectiveness Of Subsea Pipeline Leak Detection Methods - Hamzah Hamzah (Collaborate Engineering Daily Book Series, 2023)
The oil and gas exploration and production industry significantly contributes to the global economy, and undersea pipelines are the safest and most economical route to transport natural gas and crude oil from offshore to land. However, undersea pipeline networks are prone to leaks that can cause financial losses and extreme environmental pollution. Therefore, it is essential to monitor pipelines to detect leaks promptly or even predict leaks to reduce the impact of oil spills on society. Various leak detection methods have been developed, and further research is needed to identify research gaps for future work. There are various methods for detecting pipe leaks, each with advantages and disadvantages. External-based methods tend to be more accurate in finding leaks, while internal/computational methods can determine the level of leaks. The acoustic method is considered the most efficient for inspecting subsea pipelines and detecting leaks. However, each method has strengths and limitations that must be considered before choosing the proper method. Advances in computing technology have also enabled the use of dynamic modeling approaches more popular in the oil and gas industry. Factors such as cost, sensitivity, accuracy, ease of use, and the type and location of the pipeline also need to be considered in selecting a suitable pipeline leak detection method.